Engineered yeast: a breakthrough in targeted cancer therapies - Dantas, Gautam (Henry Stewart Talks, 2026)
Chemical biology–driven cancer therapeutics, Preclinical cancer models; Mechanisms of tumour modulation, Translational oncology research;Therapeutic delivery strategies, Future directions in cancer treatment